2008
DOI: 10.1111/j.1442-200x.2007.02524.x
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline‐associated seizures and their clinical characterizations

Abstract: In infants with idiopathic low seizure threshold and fever, theophylline administration might possibly trigger a seizure. Moreover, based on these patients' clinical findings, some kind of cerebral vascular involvements is speculated to be related with TAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Interestingly, TAS is most common in pediatric patients under 5 years of age (Korematsu et al 2008; Yoshikawa 2007), which can be considered to be naïve to theophylline or caffeine. In a recent study of eight pediatric TAS cases without underlying epilepsy, all had fever at the onset of TAS (> 38 °C), and six out of eight had a family history of febrile seizures and/or idiopathic epilepsy (Korematsu et al 2008).…”
Section: B Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, TAS is most common in pediatric patients under 5 years of age (Korematsu et al 2008; Yoshikawa 2007), which can be considered to be naïve to theophylline or caffeine. In a recent study of eight pediatric TAS cases without underlying epilepsy, all had fever at the onset of TAS (> 38 °C), and six out of eight had a family history of febrile seizures and/or idiopathic epilepsy (Korematsu et al 2008).…”
Section: B Clinical Findingsmentioning
confidence: 99%
“…In a recent study of eight pediatric TAS cases without underlying epilepsy, all had fever at the onset of TAS (> 38 °C), and six out of eight had a family history of febrile seizures and/or idiopathic epilepsy (Korematsu et al 2008). The authors of this study concluded that in infants with an idiopathic reduced seizure threshold and fever, theophylline administration might possibly be sufficient to trigger a seizure.…”
Section: B Clinical Findingsmentioning
confidence: 99%
“…Methylxanthines like caffeine, aminophylline or theophylline are the gold standard for countering apnea of prematurity, but convulsive seizures can occur as a serious side effect (Delanty et al, 1998;Bhatia, 2000;Korematsu et al, 2008;El-Bitar & Boustany, 2009). Such seizures originate from cortico-hippocampal networks that are yet immature at birth (Khazipov & Luhmann, 2006;Ben-Ari et al, 2007;Sipilä & Kaila, 2008;Rakic, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…But recent papers have reported that theophylline can induce convulsions. [2][3][4] With respect to the relationship between convulsive disorders and histaminic drugs, Churchill and Gammon [5] fi rst reported that antihistamines, such as diphenhydramine and tripelennamine, activated epileptic discharges on electroencephalography (EEG) and produced clinical manifestations of psychomotor seizures in adult epileptic patients. Drugs such as theophylline, antihistamines, and antiallergics with antihistaminic actions have been shown to induce febrile seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs such as theophylline, antihistamines, and antiallergics with antihistaminic actions have been shown to induce febrile seizures. [2][3][4][5][6][7][8] In the patients who are suspected of having drug-induced febrile seizures, however, reproducibility is not high, and other factors, such as fever and infection, can induce febrile seizures. Furthermore, the relationship between febrile seizures and medications has not been actively investigated.…”
Section: Introductionmentioning
confidence: 99%